Women's Representation in Politics: Impression Management Strategies in Responding to Gender-Based Challenges Among Female Politicians in Indonesia - Ratriastu Ruciswandaru; Elizabeth Kristi Poerwandari (Interdisciplinary Social Studies, 2025)
Women's political representation in Indonesia continues to face gender-based challenges, including social expectations, leadership stereotypes, and pressures related to multiple roles. This study aims to explore how female politicians interpret and respond to these challenges through impression management strategies, and how they develop psychological resilience within a gender-biased political environment. Using a qualitative case study approach, data were collected through in-depth interviews with six female politicians from various political levels and party backgrounds. The findings reveal that female politicians are aware of the conflicting expectations they face—being expected to appear feminine while simultaneously demonstrating assertiveness as leaders. In response, they employ various impression management strategies such as ingratiation, exemplification, and self-promotion in an adaptive and context-sensitive manner, aligned with conservative and religious sociopolitical settings. Despite emotional pressures stemming from gender stereotypes, they exhibit resilience through social support, emotion regulation, and strong intrinsic motivation. This study highlights that impression management is not merely a tool for maintaining public image but also a means of negotiating gender identity and roles within political spaces. These findings contribute to a deeper understanding of the psychological dynamics of female leadership and support the development of a more inclusive and gender-equitable political environment.